Does Large Igneous Province Volcanism Always Perturb the Mercury Cycle? Comparing the Records of Oceanic Anoxic Event 2 and the End-cretaceous to Other Mesozoic Events - Ruhl, Micha; Percival, Lawrence M.E.; Jenkyns, Hugh C.; Mather, Tamsin A.; Dickson, Alexander J.; Batenburg, Sietske J.; Hesselbo, Stephen P.; Barclay, Richard; Jarvis, Ian; Robinson, Stuart A.; Woelders, Lineke (My University, 2018)
Mercury (Hg) is increasingly being used as a sedimentary tracer of Large Igneous Province (LIP) volcanism, and supports hypotheses of a coincidence between the formation of several LIPs and episodes of mass extinction and major environmental perturbation. However, numerous important questions remain to be answered before Hg can be claimed as an unequivocal fingerprint of LIP volcanism, as well as an understanding of why some sedimentary records document clear Hg enrichment signals whilst others do not. Of particular importance is evaluating the impact of different volcanic styles on the global mercury cycle, as well as the role played by depositional processes in recording global Hg-cycle perturbations. Here, new mercury records of Cretaceous Oceanic Anoxic Event 2 (OAE 2: ∼94 Ma) and the latest Cretaceous (∼67–66.0 Ma) are presented. OAE 2 is associated with the emplacement of multiple, predominantly submarine, LIPs; the latest Cretaceous with subaerial volcanism of the Deccan Traps. Both of these connections are strongly supported by previously published trends towards unradiogenic osmium- (Os) isotope values in globally distributed sedimentary records. Hg data from both events show considerable variation between different locations, attributed to the effectiveness of different sediment types in registering the Hg signal, with lithologically homogeneous records documenting more clear Hg enrichments than sections with major changes in lithology such as limestones to claystones or organic-rich shales. Crucially, there is no geographically consistent signal of sedimentary Hg enrichment in stratigraphic records of either OAE 2 or the latest Cretaceous that matches Os-isotope evidence for LIP emplacement, indicating that volcanism did not cause a global Hg perturbation throughout the entire eruptive history of the LIPs formed at those times. It is suggested that the discrepancy between Os-isotope and Hg trends in records of OAE 2 is caused by the limited dispersal range of Hg emitted from submarine volcanoes compared to the global-scale distribution of Os. A similar lack of correlation between these two proxies in uppermost Cretaceous strata indicates that, although subaerial volcanism can perturb the global Hg cycle, not all subaerial eruptions will do so. These results highlight the variable impact of different volcanogenic processes on the efficiency of Hg dispersal across the globe. Factors that could influence the impact of LIP eruptions on the global mercury cycle include submarine versus subaerial volcanism, volcanic intensity or explosivity, and the potential contribution of thermogenic mercury from reactions between ascending magma and surrounding organic-rich sediments.
PUBLISHED
Keywords: Mercury; Cenomanian-Turonian OAE; End-Cretaceous; Large Igneous Province; Volcanic style; Depositional environment